KEPENTINGAN VIETNAM MEMPERBAIKI HUBUNGAN DIPLOMATIK DENGAN AMERIKA SERIKAT PASCA EMBARGO - Rwanda, Ryan; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Vietnam and United States of America make a reconciliation in their bilateral relationsip. This reconciliation was marked by the embargo’s retraction that given by the US to Vietnam in 19 . Historically, the two countries doesn’t have a good relationship in a long time. Vietnam is a country that have a communist ideology that contradict the ideology of US, which is liberal.This research theoretically has built by using Realist theory and realist point of view. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods.This research also using nation-state as the level of analyze, the focus on this research isexplain the causes of reconciliation between Vietnam and US according to This research proves that Vietnam need an ally from superpower country to maintain their sovereignty and the welfare of it’s people. US in the other hand, need to keep their influence in that region.Reseacrher has formulated the hypothesis answer which proved that both Vietnam and US have their own interests in this reconciliation of bilateral relationship. Keywords : Billateral relationship’s reconciliation, Communist ideology, Embargo’s retraction.